Assessing Default Risks for Chinese Firms : A Lost Cause? - Law, Daniel; Roache, Shaun (Washington, D.C. : International Monetary Fund, 2015)
Assessing default risks for Chinese firms is hard. Standard measures of risk using market indicators may be unreliable because of implicit guarantees, the large role played by less-informed investors, and other market imperfections. We test this assertion by estimating stand-alone 1-year default probabilities for non-financial firms in China using an equity-based structural model and debt costs. We find evidence that the equity measure of default risk is sensitive to a firm's balance sheet health, profitability, and ownership; specifically, default probabilities are higher for weaker, less profitable, and state-owned firms. In contrast, measures based on the cost of debt seem largely detached from fundamentals and instead determined by implicit guarantees. We conclude that for individual firms, equity-based measures, while far from perfect, provide a better measure of stand-alone default risks than borrowing costs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet